Monetary Policy Reaction Functions in the OECD - Sutherland, Douglas (OECD Economics Department Working Papers, 2010)
Monetary policy reaction functions can provide insights into the factors influencing monetary policy decisions. Empirical estimates suggest that differences exist across countries as to whether monetary policy reacts solely to expected inflation or also takes into account expected output developments. A range of other factors, such as monetary policy in large economies, can also influence monetary policy reactions in smaller ones. On the other hand, monetary policy has reacted less to contemporaneous measures of the output gap, while asset price developments do not generally appear to have influenced monetary policy decisions